Hydrogen production by proton exchange membrane water electrolysis using cobalt and iron hexachloroclathrochelates as efficient hydrogen-evolving electrocatalysts. (16th November 2017) - Grigoriev, S.A.; Pushkarev, A.S.; Pushkareva, I.V.; Millet, P.; Belov, A.S.; Novikov, V.V.; Belaya, I.G.; Voloshin, Y.Z.
Abstract: Cobalt and iron(II) hexachloroclathrochelates with apical aliphatic and aromatic substituents were synthesized and characterized using cyclic voltammetry. The obtained clathrochelate-based systems were impregnated on the surface of carbon paper and tested as cathode electrocatalysts in water electrolysis cell with proton exchange membrane (PEM). Both the cyclic voltammograms and the current–voltage performances of membrane-electrode assemblies suggested that these cage complexes can be successfully implemented in PEM water electrolyzers and used as efficient electrocatalysts for hydrogen evolution. Graphical abstract: Synthesis of the Co and Fe hexachloroclathrochelates and corresponding current–voltage performances of PEM water electrolysis cell. Highlights: Alkyl- and arylboron-capped Co and Fe hexachloroclathrochelates were synthesized. Clathrochelate-based electrocatalysts were implemented in PEM water electrolysis. Fe and Co clathrochelate complexes were successfully used as efficient HER catalysts. Best performances were observed with electrocatalyst based on iron(II) cage complex.